Organizing the State of Practice on Technical Debt Prevention, Monitoring, and Payment in Software Projects - Freire, Sávio; Spínola, Rodrigo; Mendonça, Manoel (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft); 2024: Anais Estendidos do XV Congresso Brasileiro de Software: Teoria e PráticaDO - 10.5753/cbsoft_estendido.2024.4115, 2024)
Knowing technical debt (TD) prevention, monitoring, and payment practices can help development teams choose the best practices for their projects. Identifying the practice avoidance reasons that lead to non-prevention, non-monitoring, and non-payment of TD can support teams in increasing their ability to manage TD items. This Ph.D. dissertation aims to investigate the state of practice in managing TD items in software projects through the continuous and independent replicating of a family of globally distributed surveys named InsighTD. We conducted a literature review on TD prevention, monitoring, and payment and then analyzed data collected by six InsighTD replication teams. The results yielded three types of artifacts: (1) an updated TD conceptual model, (2) a set of TD management maps, and (3) the IDEA diagrams listing TD Impediments, Decision factors, Enabling practices, and Actions. Lastly, we assessed these artifacts through empirical studies in academia and industry.